Drag king - O'Dwyer, Simon, 1969- (1996)
"Melbourne's drag king community put on their best pants for their annual gala night in Prahran to celebrate arts achievements in the gay community. Assigned by The Age newspaper to cover this particular section of the community, I created a mobile studio on the premises to record the personalities of the evening. Halfway through recording my subjects I was bombarded with the humoured protests of the drag queen community who believed they were more beautiful and interesting. Photographed on a Mamiya RZ camera under portable studio lights."--Simon O'Dwyer.
Part of collection: Simon O'Dwyer collection of photographs.
Title supplied by photographer.
Also available online
Keywords: Transvestites -- Victoria -- Melbourne -- Photographs; Drag balls -- Victoria -- Melbourne -- Photographs